Day 2 Tue, September 15, 2015 2015
DOI: 10.2118/175562-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Production in Slanted Horizontal Wells in Tight Reservoirs

Abstract: Economic production from tight-oil formations requires the same hydraulic fracturing techniques used during production of shale gas, and the same horizontal well technology is often used. Tight-oil formations are heterogeneous and greatly vary over relatively short distances. Thus, even in a single horizontal drilled hole, the amount recovered can vary, just as recovery within a field or even between adjacent wells can vary. This can make evaluation and decisions regarding profitability difficult. In relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The time at the end of the linear flow can be estimated by using the time at the end of half‐slope. Previous studies have shown that pressure propagation reaches the boundary before the end of half‐slope . The time at the end of the linear flow of a multifracture horizontal well is approximately 0.32 times at the end of the half‐slope (ie, t elf = 0.32 t ehs ) according to Tabatabaie et al Therefore, the time at which the liner flow ends is about 12.8 days.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The time at the end of the linear flow can be estimated by using the time at the end of half‐slope. Previous studies have shown that pressure propagation reaches the boundary before the end of half‐slope . The time at the end of the linear flow of a multifracture horizontal well is approximately 0.32 times at the end of the half‐slope (ie, t elf = 0.32 t ehs ) according to Tabatabaie et al Therefore, the time at which the liner flow ends is about 12.8 days.…”
Section: Resultsmentioning
confidence: 89%
“…Previous studies have shown that pressure propagation reaches the boundary before the end of half-slope. 17,22 The time at the end of the linear flow of a multifracture horizontal well is approximately 0.32 times at the end of the half-slope (ie, t elf = 0.32t ehs ) according to Tabatabaie et al 26 Therefore, the time at which the liner flow ends is about 12.8 days. The matrix permeability is computed to be 0.051 md, according to Equation (1).…”
Section: Verification Of the Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the volume of published literature [26][27][28][29][30][31][32][33][34][35][36][37][38] on the recovery efficiencies of different well types, to the best of our knowledge, there has been no research on the performance of highly deviated wells in the highly heterogeneous shallow reservoirs of the Central African Rift Valley region, which are significantly different from most moderate-depth to deep reservoirs in other parts of world. This is because of (i) the complications associated with drilling along a precise path within an inclined path, (ii) difficulties encountered in preventing sand influx, and (iii) challenges encountered during screen installation for sand production control, which render directional drilling more difficult and time-consuming for complex reservoirs.…”
Section: Introductionmentioning
confidence: 99%